An Exploratory Investigation into the Understanding of Keratoconjunctivitis Among Staff Nurses at SCPM Hospital in Gonda - Ahalya P.; Pooja Verma; Pooja Gupta; Pooja Yadav (International Journal of Community Health Nursing And Practices, 2024)
Background: The primary aim of the present research was to evaluate the comprehension of keratoconjunctivitis among SCPM Hospital staff nurses in Gonda. Methodologically, the study was grounded in the general system theory proposed by Ludwig von Bertalanffy in 1968. To fulfill this aim, a non-experimental descriptive research design was utilized. The study included a sample of 40 SCPM Hospital staff nurses in Gonda who met the predefined inclusion criteria. Purposive sampling, a non-probability method, was utilized for participant selection. A structured sociodemographic data, knowledge questionnaire on keratoconjunctivitis were selected on the basis of the objective of the study. Result: The overall score of knowledge among staff nurses were as follows: 19 (47.5%) inadequate knowledge, 14 (35.0%) moderate knowledge, and 7 (17.5%) adequate knowledge. Conclusion: The hypothesis was not accepted. The chi-square analysis suggests that there was no statistically significant association between knowledge and the selected sociodemographic factors.
Keywords: Keratoconjunctivitis; descriptive research design; knowledge score; socio-demographic factors; staff nurses